Preparation and characterization of novel hybrid of chitosan-g-PDMS and sodium montmorrilonite - Depan, Dilip; Kumar, Bijandra; Singh, Raj Pal (Journal of Biomedical Materials Research Part B-Applied Biomaterials, 2008)
Preparation and properties of Chitosan (CS)-clay nanocomposites grafted with polydimethyl siloxane (PDMS) with different clay ratios are herein discussed. CS is intercalated into sodium montmorrilonite and PDMS is grafted onto CS under UV irradiation. Sample films of CS intercalated into clay and grafted with PDMS were prepared by solvent casting method with varying amount of nanoclay and PDMS. They were characterized by conventional techniques such as X-ray diffractometry, fourier transform infrared spectroscopy, C-13 NMR, thermo gravimetric analysis, and differential thermal analysis. Sorption behavior of samples has been followed by measuring swelling degree and issues on the interactions of biopolymers with clay are also discussed. The water absorption of composites films reduces with an increase in the amount of incorporated clay. This is due to the barrier formation in the form of cross-linking points, which prevents water permeation into CS. The amount of adsorbed water is more, when the amount of CS exceeds the amount of PDMS. This shows high water retention capacity of CS. (c) 2007 Wiley Periodicals, Inc.
Keywords: Chitosan; graft copolymerization; Nanocomposites; PDMS; water absorption